Basics on Water Injection Process for Gasoline Engines. (August 2018) - Falfari, Stefania; Bianchi, Gian Marco; Cazzoli, Giulio; Forte, Claudio; Negro, Sergio
Abstract: Actual and future limits to the global CO2 emissions and the necessity of a further reduction of the fossil non-renewable fuels have moved the automotive engine research toward new solutions. With focus on reciprocating internal combustion engines, the mass of CO2 emitted in the atmosphere is a function of the fuel consumption. Therefore, the designers are focusing their attention on both the drop of passive resistances and the improvement of the engine efficiency. As far as the latter is concerned, the reduction of in-cylinder temperature and the adoption of stoichiometric combustion on the full range of engine operation map are the most investigated solutions. Water injection is thought to help in fulfilling these goals thus contributing towards more efficient engines. The aim of the present work is to understand the basic thermophysical and chemical fundamentals governing the water injection application in modern downsized spark ignited engines. The investigation has been carried out with aid of CFD simulation by using AVL FIRE v.2017 solver.